Unexpected Exacerbation of Tracheal Stenosis in a Patient with Hunter Syndrome Undergoing Cardiac Surgery - Nobue Terabe; Soichiro Yamashita; Makoto Tanaka (Case Reports in Anesthesiology)
We report unexpected exacerbation of tracheal stenosis during general anesthesia in a 50-year-old patient with Hunter syndrome undergoing cardiac surgery for valvular disease. He had undergone cervical laminoplasty 3 months previously; at that time, his airway had been uneventfully managed. Preoperative flexible fiberoptic laryngoscopy showed a normal upper respiratory tract, but chest computed tomography showed tracheal stenosis that had flattened the lumen. The narrowest part above the tracheal bifurcation was 2 cm long and the anteroposterior diameter was ≤6 mm. Cardiac surgery was uneventfully performed. After weaning from cardiopulmonary bypass, the tidal volume suddenly decreased from 450 to 120 ml at sternal closure. The end-expiratory carbon dioxide pressure increased from 39 to 71 mmHg. Bronchoscopic examination showed that the part of tracheal bifurcation was almost occluded. A tidal volume of 400 ml was obtained after the transesophageal echocardiography probe was removed and the peak inspiratory pressure increased. Although extubation was performed on the second postoperative day, procaterol inhalation and noninvasive positive-pressure ventilation were needed for 3 days because of wheezing and dyspnea. In conclusion, the risk of lower respiratory tract obstruction should be considered during general anesthesia in patients with Hunter syndrome with collapsible tracheal stenosis undergoing cardiac surgery.